Encyclopedia of modern ethnic conflicts - Rudolph, Joseph R. 1942- (Joseph Russell).; Gale Group (Santa Barbara, California ABC-CLIO, an imprint of ABC-CLIO, LLC, 2016)
This work uses case studies to explore acts of violence between ethnic or national communities inside individual states, making it an ideal reference to quickly gain an understanding of ethnic struggles.
volume 1. Armenia to Lebanon -- volume 2. Malaysia to Western Sahara.
Includes bibliographical references.
Keywords: Ethnic relations -- Political aspects -- Encyclopedias; Culture conflict -- Encyclopedias; World politics -- 1995-2005 -- Encyclopedias